(untitled) (Swiss Medical Weekly, 2011)
BACKGROUND: In 2002, Swiss citizens voted to accept new laws legalising the termination of pregnancy (TOP) up to 12th week of pregnancy. As a result the cantons formulated rules of implementation. Health institutions then had to modify their procedures and practices. QUESTIONS UNDER STUDY/PRINCIPLES: One of the objectives of these changes was to simplify the clinical course for women who decide to terminate a pregnancy. Have the various health institutions in French-speaking Switzerland attained this goal? Are there differences between cantons? Are there any other differences, and if so, which ones? METHODS: Comparative study of cantonal rules of implementation. Study by questionnaire of what happened to 281 women having undergone a TOP in French-speaking Switzerland. Quantitative and qualitative method. RESULTS: The comparative legal study of the six cantonal rules of implementation showed differences between cantons. The clinical course for women are defined by four quantifiable facts: 1) the number of days to wait between the woman’s decision (first step) and TOP; 2) the number of appointments attended before TOP; 3) the method of TOP; 4) the cost of TOP. On average, the waiting time was 12 days and the number of appointments was 3. The average cost of TOP was 1360 CHF. The differences, sometimes quite large, are explained by the size of the institutions (large university hospitals; average-sized, non-university hospitals; private doctors’ offices). CONCLUSIONS: The cantonal rules of implementation and the size of the health care institutions play an important role in these courses for women in French-speaking Switzerland.